2023
DOI: 10.1029/2022jf006727
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Quantify Sediment Transfer and Storage in Rivers—Testing Feldspar Single‐Grain pIRIR Analysis and Numerical Simulations

Abstract: Quantifying sediment transport and storage in fluvial systems is fundamental for understanding the transfer of eroded materials from source to sink. Here, we investigated the potential of a combined approach using a luminescence measured in modern fluvial sediments and numerical simulations to quantify transport and storage in rivers. We acquired luminescence data at the single‐grain scale on feldspar sediments of Waimakariri and Rakaia braided rivers (New Zealand) using a post infra‐red infra‐red stimulated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…Several studies have indicated progressive bleaching downstream (e.g. Guyez et al, 2023), and previous work in the Holocene Rhine delta indicated relatively well-bleached OSL signals even for deposits formed in the past centuries Hobo et al, 2014).…”
Section: Optically Stimulated Luminescence Methodology and Resultsmentioning
confidence: 99%
“…Several studies have indicated progressive bleaching downstream (e.g. Guyez et al, 2023), and previous work in the Holocene Rhine delta indicated relatively well-bleached OSL signals even for deposits formed in the past centuries Hobo et al, 2014).…”
Section: Optically Stimulated Luminescence Methodology and Resultsmentioning
confidence: 99%
“…More data should be collected to estimate ξ using this method. Other new datasets and techniques, such as sediment transit time estimates using cosmogenic nuclide concentrations (e.g., Repasch et al, 2020;Wittmann et al, 2011) or luminescence (e.g., Guyez et al, 2023) and datasets of "smartrock" tracer transport(e.g., Pretzlav et al, 2021), can provide additional constraints on the sediment transport dynamics in river system and shed light on the value of ξ in natural system.…”
Section: The Value Of ξ Controls the Behavior Of Erosion-deposition S...mentioning
confidence: 99%